Neoliberal reforms and ideological spokespersons: accumulation of capital and landowning class in Argentina in the 1990s. The case of Sociedad Rural Argentina - Pérez Trento Nicolás (Sociedad y Economía, 2018)
The implementation of neoliberal economic regimes in different Latin American countries in the early 1990s did not necessarily had the general acceptance of capitalists in the industrial sector. In Argentina, in contrast to the political action of these, the most concentrated fraction of the landowning class was constituted as one of the social subjects that acted most significantly to implement the economic reforms in their sector. In this paper, which displays the Argentine case, the actions of these social subjects are synthesized based on newspaper notes, as well as on documents of the associations and secondary bibliography.